Family support, enriched preschool and serious youth offending - Allen, Jacqueline (Trends & issues in crime and criminal justice, 2024)
This paper investigates the effects on court-adjudicated offending to age 17 of comprehensive, community‑based support offered through the Pathways to Prevention Project to families of preschool and primary age children. The sample is 543 children from a disadvantaged region in Brisbane, 192 of whom, at age four in 2002 or 2003, participated in the standard preschool curriculum plus a program designed to strengthen oral language and communication skills, and who transitioned to a local primary school where family support remained available. Family support (involving 41% of families) was associated overall with a heightened risk of offending, reflecting the high level of need in these families, particularly in the later primary years. However, family support combined with the communication program corresponded to a very low offending rate. This suggests that family support should be combined with both high-quality, early-in-life preventive initiatives and with evidence-based child and parent programs in late primary school.